Tech-Driven Banking Revolution: A Bibliometric Analysis and‎Visualization of Neobanking Research Using Biblioshiny,‎Vosviewer and Citespace - Cherian, Aiswarya; M P, Dinesh; John, Josiah; Joseph, Dawn; T, Suresh; Jose, Jobin (International Journal of Accounting and Economics Studies, 2025)
Neobanking refers to digital-only banking platforms that deliver financial services exclusively through mobile applications and web interfaces, without the need for physical branches. This bibliometric analysis investigates the global research landscape on neobanking using data ‎retrieved from the Scopus database. The study employs three specialized tools—Biblioshiny, VOSviewer, and CiteSpace—to analyze publication trends, scholarly impact, and thematic development within the domain. Key findings highlight a steady rise in scientific output, particularly after 2015, with significant contributions from countries such as Indonesia, India, and the United States. The analysis identifies top ‎influential researchers and journals that have shaped the discourse across finance, technology, and digital transformation. Visual network ‎analyses reveal co-authorship patterns, intellectual linkages through co-cited authors and journals, and document-level connections via bibliographic coupling. Keyword co-occurrence maps and thematic evolution charts trace the shift from financial inclusion and mobile banking to ‎recent emphases on fintech, trust, and digital transformation. The thematic map classifies motor themes like digital banking and neobanks as ‎well-developed and central, while signaling emerging interest in user experience and regulatory frameworks. Trend analysis underscores a ‎transition from foundational access-based models to innovation-driven financial ecosystems. The study concludes by identifying research ‎gaps and practical implications, emphasizing the need for integrative approaches that address technological, behavioral, and regulatory ‎dimensions of neobanking‎.